ANGIOTENSIN CONVERTING ENZYME INHIBITOR SEBAGAI TERAPI PASIEN HIPERTENSI PRIMER DENGAN OBESITAS - Muhamad Jiofansyah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2019)
Hypertension and obesity are the diseases that’s corelate to each other. The Bridge thatconnects between hypertension and obesity lies on Renin Angiotensin System (RAS) andleptin and adiponectin hormone system. RAS function to regulate the osmolarity of theblood circulation to control blood pressure. Leptin is a hormone that inhibit food intake.Adiponectin secreted by adipose cells to regulate blood glucose and performing theoxidation of fatty acid. In recent studies found that there’s a correlation betweenangiotensinogen with adiponectin. Then the question emerge about an intervention on RAScould have an effect on adiponectin, the hormone that’s corelate to obesity. A study fromFontana et.al found that there’s a correlation on using ACE inhibitor with leptin andadiponectin. Subjects with primary hypertension with 8 weeks enalapril therapy shows anincrease in adiponectin level, whilst the control group didnt show any significant change.There isn’t any correlation between subject and control on leptin level. This journal maypresent the theories that may lead to explaining about the correlation between hypertensionand obesity, and if ACE Inhibitor is the right therapy for primary hypertension patient withan obesity or not.